PENGARUH PENERAPAN MEDIA POSTER DALAM PROJECT BASED LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMAN 5 PADANG - Almutia Lima; Mahrizal Mahrizal; Hidayati Hidayati (PILLAR OF PHYSICS EDUCATION, 2015)
Learning outcomes optimal not yet, this is caused by lack of interest and active student in learning process, so the teacher should cermat choose the media and learning model to support the learning process. To increase interest and activity students, the teacher can apply poster media in Project Based Learning. The type this research is Quasi Exsperiment research with Randomized Control Group Only Design. The population in this research all of the students of SMAN 5 Padang in the first semester of academic year 2014/2015. Sample is determined by purposive sampling technique. The data of the research are the students learning outcomes in the domains of cognitive, affective, and phychomotor. The result of this research show that the mean of students learning outcomes of the experimental class is higher than the control class in  three domains. Based on the data analysis result, it is gotten that three is significance different learning outcomes between experiment and control class at 005 sognificance level, so can conclude using poster in Project Based Learning influence students of SMAN 5 Padang learning outcomes